Implementasi Penggunaan Media Pembelajaran Interaktif Terhadap Hasil Belajar Siswa Di Sekolah Dasar - Salma Nanda Ardelia; Gloria Yulianti; Vicky Fatmawati; Nela Rofisian (CV. ITTC INDONESIA, 2024)
This journal discusses the implementation of learning media on improving student learning outcomes in elementary schools. The purpose of this study is to understand how effective the use of learning media is in supporting students in understanding the material presented. With the development of the modernization era, teachers can now take advantage of learning media to create innovations and improve teaching methods in the classroom. The results of the literature study conducted show that learning media has a significant influence. This is because the media allows students to see firsthand the material being taught, which makes learning easier to understand and more engaging for them.